2014
DOI: 10.1038/ja.2014.35
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal effect of Gatifloxacin and copper ions combination

Abstract: It is a well-known fact that to bring a new molecule it may take more than a decade. The existing drugs, which are known for their adverse reaction or toxicity, if utilized and allowed in different formulation, the new effective formulation may be discovered and developed. This may help in reducing various side effects, time and costs. In this study, fungal infection was inoculated superficially over the skin of guinea pigs and treated with the broad-spectrum antimicrobial (gatifloxacin) in combination with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Similar mechanisms of action have been proposed for the two metals. Copper, similar to silver, has been tested in combination with antibiotics and has shown synergy with the antifungal agent gatifloxacin 145 and the antitubercular drugs capreomycin 146 and disulfiram 147 ; for disulfiram, no other bivalent transition metals (for example, Fe 2+ , Ni 2+ , Mn 2+ and Co 2+ ) were effective. One study has shown that the bacterial toxicity of copper may be related to its effects on the stability of folded proteins — both increased and decreased — with proteins involved with the ribosome and protein biosynthesis, and cell-redox homeostasis particularly affected 148 .…”
Section: Antibacterial Strategies Based On Metal Uptakementioning
confidence: 99%
“…Similar mechanisms of action have been proposed for the two metals. Copper, similar to silver, has been tested in combination with antibiotics and has shown synergy with the antifungal agent gatifloxacin 145 and the antitubercular drugs capreomycin 146 and disulfiram 147 ; for disulfiram, no other bivalent transition metals (for example, Fe 2+ , Ni 2+ , Mn 2+ and Co 2+ ) were effective. One study has shown that the bacterial toxicity of copper may be related to its effects on the stability of folded proteins — both increased and decreased — with proteins involved with the ribosome and protein biosynthesis, and cell-redox homeostasis particularly affected 148 .…”
Section: Antibacterial Strategies Based On Metal Uptakementioning
confidence: 99%
“…Recently, Festa et al have published a novel approach that allows accumulation of copper in pathogen cells without activating its Cu-resistant mechanisms and significantly increases selectivity of the treatment (Festa et al 2014). In other strategies, Cu(II) ions have been either utilized as carriers for known antibiotics, allowing them to bypass existing efflux-mediated resistance to drugs (Manning et al 2014;Lopes et al 2013;Shams et al 2014), or as chelators that upon binding to a ligand, change its conformation to the Bactive^mode (Haeili et al 2014). Several potent copper chelators with activity against MRSA and Mycobacterium tuberculosis strains have been identified through drug screening assays specifically designed for identification of copper-dependent antimicrobial compounds (Speer et al 2013) with, potentially, more discoveries on the way.…”
Section: Copper and Zinc Resistance In Gram-positive Bacteriamentioning
confidence: 99%
“…Copper nanoparticles showed a strong antifungal effect against agriculturally important fungal phytopathogens, like Curvularia lunata , Alternaria alternate , Fusarium oxysporum and Phoma destructive , . However, there must be clarity about whether the copper is present in an ionic or nanoparticulate form, as this can impact the control of several bacterial and fungal pathogens , . Moreover, the health consequences of consuming residual copper ions and colloid forms of copper from agricultural produce are unknown , .…”
Section: Nanotechnology‐based Opportunities In Crop Protectionmentioning
confidence: 99%
“…152,153 However, there must be clarity about whether the copper is present in an ionic or nanoparticulate form, as this can impact the control of several bacterial and fungal pathogens. 154,155 Moreover, the health consequences of consuming residual copper ions and colloid forms of copper from agricultural produce are unknown. 156,157 Various metal-based nanomaterials can be possibly used for plant disease management using efficient crop protection practices, particularly to avoid the agricultural losses posed by fungal and bacterial pathogens.…”
Section: Nanotechnology-based Opportunities In Crop Protectionmentioning
confidence: 99%